The relative relevance of phosphorylation of the Thr¹⁷ residue of phospholamban is different at different levels of β-adrenergic stimulation - Said, María Matilde (2002)
Contractility and relaxation measurements were combined with the determination of total phospholamban (PLB) phosphorylation and the immunodetection of PLB-phosphorylation sites in the intact, beating rat heart to identify the contributions of PLB phosphorylation at the Thr¹⁷ and Ser¹⁶ residues at different levels of β-adrenoceptor stimulation. Whereas with 30-300 nM isoproterenol, phosphorylation of Thr¹⁷, the Ca²⁺-calmodulin-dependent protein kinase-II (CaMKII) site and Ser¹⁶, the protein kinase A (PKA) site, contributed approximately 50% each to PLB phosphorylation, and both participated in the relaxant action of isoproterenol, at lower a level of β-adrenoceptor stimulation (isoproterenol 0.3-3 nM), both effects were exclusively due to Ser¹⁶ phosphorylation. Increasing [Ca]o at 3 nM isoproterenol, to obtain an increase in contractility comparable to that produced by 30 nM isoproterenol, significantly increased Thr¹⁷ phosphorylation and the relaxant effect produced by 3 nM isoproterenol. An increase in Thr¹⁷ phosphorylation and in the relaxant effect of 3 nM isoproterenol was also obtained by phosphatase inhibition (okadaic acid). In this case, Ser¹⁶ phosphorylation was also increased. Moreover, perfusion with 30 nM isoproterenol in the presence of the PKA inhibitor H-89 decreased phosphorylation at both PLB residues and diminished the inotropic and relaxant responses to the β-agonist. The relative contribution of Thr¹⁷ phosphorylation to the isoproterenol-induced phosphorylation of PLB and relaxation thus increased with the level of β-adrenoceptor stimulation and the consequent increase in PKA activity. The lack of Thr¹⁷ phosphorylation at low isoproterenol concentrations might therefore be attributed to a level of PKA activity insufficient to increase [Ca]i to activate the CaMKII system and/or to inhibit the phosphatase that dephosphorylates PLB.